A CASE OF RARE CONGENITAL HEART MALFORMATION: TAUSSIG- BING SYNDROME - Milena Gulinac; Georgi Ivanov; Ivan Tsranchev; Penka Stefanova; Simeon Lichev (Science & Research)

(untitled)
Introduction- Taussig- Bing Syndrome is a rare congenital heart malformation that was first described by Helen Taussig and Richard Bing. The aim of this article is to show the main morphological changes in this case of rare congenital malformation. Performed methods were autopsy examination, clinical data analysis, x-ray examination and microscopic examination. Results- the index case is 34 days- old male newborn, born in 37 gestational age, with weight 2.150gr. and height- 45 cm. The heart was found enlarged with normal position in the chest. During dissection of the heart there were detected: hypertrophy and dilation of the right ventricle; the aorta arise entirely above the right ventricle; the dilated pulmonary valve does not override the left ventricular cavity; pulmonary artery arises primarily from the right ventricle and partially overrides the ventricular septum and a high and large sub- pulmonary ventricular septal defect. Conclusions- The treatment of this syndrome is continuing to be an actual medical problem. The right diagnose and the adequate treatment can widely reduce the mortality and morbidity from this disease.